Lung Transplant Improves Survival and Quality of Life Regardless of Telomere Dysfunction - Planas-Cerezales, Lurdes; Arias-Salgado, Elena G.; Berastegui, Cristina; Montes-Worboys, Ana; González-Montelongo, Rafaela; Lorenzo-Salazar, José. M.; Vicens-Zygmunt, Vanesa; Garcia-Moyano, Marta; Dorca, Jordi; Flores, Carlos; Perona, Rosario; Román, Antonio; et al. (Frontiers in Medicine, 2021)
Introduction: Fibrotic interstitial lung diseases (ILDs) are the first indication for lung transplantation (LT). Telomere dysfunction has been associated with poor post-transplant outcomes. The aim of the study was to evaluate the morbi-mortality and quality of life in fibrotic ILDs after lung transplant depending on telomere biology. Methods: Fibrotic ILD patients that underwent lung transplant were allocated to two arms; with or without telomere dysfunction at diagnosis based on the telomere length and telomerase related gene mutations revealed by whole-exome sequencing. Post-transplant evaluation included: (1) short and long-term mortality and complications and (2) quality of life. Results: Fifty-five percent of patients that underwent LT carried rare coding mutations in telomerase-related genes. Patients with telomere shortening more frequently needed extracorporeal circulation and presented a higher rate of early post-transplant hematological complications, longer stay in the intensive care unit (ICU), and a higher number of long-term hospital admissions. However, post-transplant 1-year survival was higher than 80% regardless of telomere dysfunction, with improvement in the quality of life and oxygen therapy withdrawal. Conclusions: Post-transplant morbidity is higher in patients with telomere dysfunction and differs according to elapsed time from transplantation. However, lung transplant improves survival and quality of life and the associated complications are manageable.